SAT0395 RESPONSIVENESS AND CLINICAL TRIAL DISCRIMINATION OF SWOLLEN AND TENDER JOINT COUNTS FOR THE MEASUREMENT OF MSK DISEASE ACTIVITY IN PSORIATIC ARTHRITIS. (June 2019) - Duarte-Garcia, Ali; Eder, Lihi; Goel, Niti; Wit, Maarten de; Gladman, Dafna D.; Fitzgerald, Oliver; Mease, Philip J.; Leung, Ying Ying; Orbai, Ana-Maria; Shea, Bev; Strand, Vibeke; Helliwell, Philip; et al.
Abstract : Background: While tender and swollen joint counts (TJC and SJC) are key instruments for the assessment of peripheral arthritis in PsA, little is known about the psychometric properties of TJC and SJC in randomized controlled trials (RCTs) and how these properties differ among patient subgroups. 1 Objectives: To assess the responsiveness and discrimination of TJC and SJC in PsA using RCT datasets and evaluate subgroups of patients with early vs. established disease and 3 or less vs 4 or more active joints. Methods: Patient-level data from 8 phase III RCTs and the TIght COntrol of Psoriatic Arthritis (TICOPA) trial were analyzed 2 . The standardized response mean (SRM, mean difference between baseline and follow up divided by the standard deviation (SD) of the mean difference) and standardized mean differences (SMD, mean difference in the treated group minus the mean difference in the placebo group divided by the pooled SD for the change) were used to address responsiveness and discrimination respectively. TJC28, SJC28, TJC68, and SJC66 were the primary measures of interest but physician and patient global assessments (PhGA and PtGA) and pain were included for comparison. SRMs were calculated in subgroups of patients with less than 3 (TJC68/SJC66 ≤ 3) or more than 3 (TJC68/SJC66) active joints as well as early (< 2 years) and established (≥2 years) disease. Results: In traditional phase III RCTs, TJC and SJC were responsive and had good clinical trial discrimination. SRMs were similar and ranged from -0.8 to -0.4 ('moderate' responsiveness) (Figure 1 ). SMDs were similar among SJC28 and SJC66 and likewise between TJC28 and TJC68 but mostly within the small effect range (-0.2 to -0.5; not shown). PhGA and PtGA had higher SMDs than the joint counts. SRMs were substantially lower for joint counts (and also PtGA) among the low compared with the higher joint count groups (Figure 2 ). There were no substantial differences in SRMs between patients with early and established disease. Conclusion: Joint counts are responsive to change and have reasonable discrimination in RCTs among patients higher disease activity at baseline. However, joint counts may not be ideal outcome measures in oligoarticular disease and have lower responsiveness and discrimination in this subgroup. References: [1] Duarte-Garcia et al. J Rheumatol 2019 In Press. [2] Coates et al. Lancet 2016 Acknowledgement: Funded by the Rheumatology Research Foundation; We would like to thank Janssen Scientific Affairs LLC, YODA (Yale Open Data Access) Project, UCB, Novartis, and Pfizer for their scientific partnership. Disclosure of Interests: Ali Duarte-Garcia: None declared, Lihi Eder Grant/research support from: AbbVie, Eli Lilly and Company, Amgen, Celgene, UCB, Janssen, Novartis, and Pfizer, Consultant for: AbbVie, Eli Lilly and Company, Amgen, Celgene, UCB, Janssen, Novartis, and Pfizer, Niti Goel Shareholder of: Own stock options in Kezar Life Sciences., Employee of: Corporate officer of Kezar Life Sciences., Maarten de Wit: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen, Celgene, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead, Janssen, Lilly, Novartis, Pfizer, and UCB, Oliver FitzGerald: None declared, Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Ying Ying Leung Grant/research support from: Abbvie, Novartis, Speakers bureau: Abbvie and Novartis, Speakers bureau: Novartis, Ana-Maria Orbai Grant/research support from: AbbVie, Celgene, Horizon Pharma, Janssen, Lilly, and Novartis, Consultant for: Lilly, Janssen, Novartis, Pfizer, and UCB, Bev Shea Employee of: Salary partially paid by OMERACT, Vibeke Strand Consultant for: AbbVie, Amgen, Bayer, BMS, Boehringer Ingelheim, Celgene, Celltrion, CORRONA, Crescendo, EMD Serono, Genentech/Roche, GSK, Horizon, Inmedix, Janssen, Kezar, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sandoz, Sanofi, Servier, UCB., Philip Helliwell Grant/research support from: Paid to charity: from AbbVie, Janssen and Novartis, Consultant for: Paid to charity: from AbbVie, Amgen, Pfizer, and UCB and Celgene. Paid to self: from Celgene and Galapagos, Alisa Stephens-Shields: None declared, William Tillett Grant/research support from: AbbVie, Celgene, and Lilly, Consultant for: AbbVie, Celgene, Lilly, Novartis, and Pfizer, Speakers bureau: Abbvie, Celgene, Lilly, Janssen, Novartis, UCB, and Pfizer, Laura C Coates Grant/research support from: AbbVie, Celgene, Lilly, Novartis and Pfizer, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead Sciences Inc., Janssen, Lilly, Novartis, Pfizer, Prothena Corp and UCB, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda